Brucellosis in Yogyakarta Slaughterhouse Workers - Setyawan Budiharta (Hemera Zoa, 1992)
The purposes of the study were (1) to measure the serological prevalance of brucellosis among Yogyakarta slaughterhouse workers, (2) to compare rapid blood test (RBT) and complement fixation test (CFT) for serologically detecting brucllosis, and (3) to evaluate the repeatability of both tests.A total of 52 blood samples, 26 from each beef and swine slughtering plants were used for the investigation. These samples cocsist of occupation from administration to blood collection, and missed only 4 workers in both plants. The samples were tested against brucllosis using RBT and CFT and read both differentially and paralelly. Both tesis were compared using McNemar's X2(kuadrat). for evaluating the repeatability of the technician.The result revealed that the RBT prevalence was 13,46%, CFT 3,85% and pararel prevalance was 15,38%. Seven of 8 reactors detected were from swine plants but did not show any significant prevalance different (P>0,05) between the two plants. The highest prevalance was found among dressing workers, however, the highest risk (50%) was found in blood collecting workers.McNemar's X2(kuadrat) did not show any prevalance difference between RBT and CFT (p>0,05) although the odds of being RBT positive was 6x as high as CFT.The repeatability of CFT and RBT was found to be 92.68% and 37.80%, respectivrly, suggesting that CFT is more stable than RBT.